Negotiating Maslaḥat and Maḍarat: Uang Panai and the Socio-Cultural Dynamics of Bugis–Makassar Customary Marriages - Syarifa Raehana; Nasriah Nasriah; Andi Herawati (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Uang panai is a central tradition in Bugis–Makassar customary marriage, functioning not only as a formal customary requirement but also as a symbolic expression of respect for women and the groom’s social and moral responsibility. This study seeks to harmonize the practice of uang panai with principles of social justice and Islamic law by proposing regulatory and normative measures that prevent it from becoming an excessive economic burden on families. The research addresses two main issues: the position of uang panai in Bugis–Makassar customary marriage from the perspectives of maslaḥah and maḍarah, and the influence of sociocultural dynamics on its contemporary practice. Employing a normative legal approach with qualitative methods, this study analyzes uang panai through the lenses of positive law, customary law, and Islamic legal principles. The analysis is supported by primary sources, including regulations, fatwas, classical fiqh texts, and customary documents, which are examined using content analysis to interpret legal norms and cultural values within current social dynamics. The findings indicate that uang panai holds a crucial position as a symbol of appreciation and a mechanism of social bonding between families, contributing to social harmony, mutual respect, and protection for wives and their families. Nevertheless, the practice may also generate economic pressure on the groom’s family and, in certain contexts, lead to exploitative tendencies. Ongoing sociocultural changes have reshaped the meaning and function of uang panai, reflecting broader socio-economic transformations and necessitating adaptive interpretations that preserve its core cultural values. The academic contribution of this study lies in its reconceptualization of uang panai as a dynamic customary institution, understood through a maslaḥah–maḍarah framework rather than as a static tradition, thereby enriching scholarship on Islamic family law and customary law through an integrative normative perspective that bridges local cultural values with principles of Islamic justice